Strength prediction of adhesively-bonded joints - Campilho, Raul D. S. G. (Taylor & Francis Group, CRC Press, 2016)
Adhesively-bonded joints provide many advantages over conventional mechanical fasteners and are increasingly receiving attention as an alternative to mechanical joints in engineering applications. The traditional fasteners usually result in the cutting of fibers and hence the introduction of stress concentrations, both of which reduce structural integrity. By contrast, bonded joints are more continuous and have potential advantages of strength-to-weight ratio, design flexibility, and ease of fabrication. This book provides an overview of available analytical methods as well as numerical methods.
"A science publishers book."
Keywords: Adhesive joints.; Strength of materials.; elektronické knihy; electronic books